1996
DOI: 10.1006/jmaa.1996.0197
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Mapping of Nonsmooth Domains via the Kerzman–Stein Integral Equation

Abstract: The connection between the Riemann map and the Szego kernel is classical. But the fact that there is an efficient numerical procedure, based on the Kerzman᎐Stein integral equation, for computing the Szego kernel of a smoothly bounded domain in the plane is more recent. In this paper it is shown how to extend the results of Kerzman and Stein to certain nonsmooth domains. This provides a new method for numerically computing the Szego kernel, and hence the Riemann map, of these domains. ᮊ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…That modification depends on both the angles and the curvature at the corners, whereas our construction only depends on the angles at the corners and it applies to a larger class of domains. We also point out work of Thomas in [10]. He showed that the Nyström solution of Eq.…”
Section: Introductionmentioning
confidence: 96%
“…That modification depends on both the angles and the curvature at the corners, whereas our construction only depends on the angles at the corners and it applies to a larger class of domains. We also point out work of Thomas in [10]. He showed that the Nyström solution of Eq.…”
Section: Introductionmentioning
confidence: 96%
“…In particular, Riemann_Map() works for domains with piecewise smooth boundary. For a justification of this point, see [Thomas 1996]. …”
Section: Introductionmentioning
confidence: 99%
“…Kerzman and Trummer [10] have derived an integral equation of the second kind, whose unique solution is the Szegö kernel. This integral equation is now called the Kerzman-Stein integral equation by some authors, see [3, p. 108], [17,13], or the integral equation of Kerzman and Trummer [7,p. 560].…”
Section: Introductionmentioning
confidence: 99%